A Comparison of Human Values Among Students From Postcommunist Turkic Republics and Turkey. (November 2013) - Dirilen-Gümüş, Özlem; Sümer, Nebi
This study aims to compare the value structure of university students from postcommunist Turkic republics and Turkey within the framework of Schwartz and Bardi's (1997) acclimation and compensation hypothesis. Participants from four Turkic republics ( N = 269; Turkmenistan, Kyrgyzstan, Kazakhstan, and Azerbaijan) and Turkey ( N = 286) completed the Portrait Values Questionnaire. The results indicated that students from postcommunist countries reported higher levels of embeddedness and lower levels of intellectual autonomy, affective autonomy, and egalitarianism than Turkish students. No difference was found regarding mastery, harmony, and hierarchy values. This study provided support for the acclimation and compensation hypothesis, except for the hierarchy values. The findings were discussed considering the continuous social change in these countries and its implications for the dynamism of value structure.